2007
DOI: 10.3200/aeoh.62.3.121-128
|View full text |Cite
|
Sign up to set email alerts
|

Health Evaluation of Gold Miners Living in a Mercury-Contaminated Village in Serra Pelada, Pará, Brazil

Abstract: Serra Pelada is a village in the Amazon region of Brazil where most of the inhabitants are former gold miners. Of 235 individuals evaluated, 219 were males (93.19%), 16 were females (6.80%), and the mean age was 52.07 years (standard deviation = 11.57). Most were heavy drinkers (62.44%) and smokers (70.30%), and 85.53% had previously suffered from malaria. Reported symptoms included fatigue (30.60%), irritability (35.62%), excitability (14.16%), insomnia (34.48%), memory loss (61.80%), visual field constrictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 8 publications
2
13
0
1
Order By: Relevance
“…This detailed article summarized the results from 26 studies, showing that the exposure to inorganic Hg vapor is high, and that toxic effects have to be considered. Some relevant papers in different countries with ASGM showed that Hg levels in any analyzed biomarker were higher compared to control groups or reference values, and in some studies clinical symptoms or negative results for subclinical parameters were identified [7,8,13,14,26,28,29,31,32,[53][54][55][56][57][58][59][60]. These results are very similar to our results.…”
Section: Literaturesupporting
confidence: 82%
“…This detailed article summarized the results from 26 studies, showing that the exposure to inorganic Hg vapor is high, and that toxic effects have to be considered. Some relevant papers in different countries with ASGM showed that Hg levels in any analyzed biomarker were higher compared to control groups or reference values, and in some studies clinical symptoms or negative results for subclinical parameters were identified [7,8,13,14,26,28,29,31,32,[53][54][55][56][57][58][59][60]. These results are very similar to our results.…”
Section: Literaturesupporting
confidence: 82%
“…Human health risks due to mercury exposure are well known with kidney damage and signs of highly devastating neurotoxicity particularly in the central and peripheral nervous systems (Aschner and Aschner 1990;Langford and Ferner 1999;Magos 1997;Tchounwou et al 2003;Zalups 2000) as prime examples. DiVerent studies (Bose-O'Reilly et al 2008;Castilhos et al 2006;Corbett et al 2007;Cortes-Maramba et al 2006;da Costa et al 2008;Peplow and Augustine 2007;van Straaten 2000a, b;Veiga et al 2006) show that mercury contamination is still an active worldwide issue for both humans and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the sensitivity in developing humans was demonstrated by the severe cognitive and physical congenital defects observed in children whose mothers were asymptomatic [11]. Inorganic mercury is a well-known renal toxicant, and occupational exposure to this metal has been associated with neurological and renal defects [7, 12, 13]. …”
Section: Introductionmentioning
confidence: 99%